Cultural Synergy in Islamic Educational Leadership: Developing an Inclusive Model for Enhancing Management Effectiveness and Educational Quality in Culturally Diverse Institutions - Walid, Ahmad; Hidayati, Suci; Ramli, Nurleli (Universitas Nurul Jadid, 2024)
This research aims to develop an ideal leadership model for Islamic educational institutions based on cultural diversity. The focus of this research is to understand how the interaction between leadership and cultural diversity affects management effectiveness and the quality of education in these institutions. This study uses a qualitative approach with a case study design, where data is collected through in-depth interviews, participatory observations, and documentation analysis in several Islamic educational institutions in Indonesia that have a high level of cultural diversity. The results show that the success of leadership in this context is highly dependent on the ability of leaders to adapt to local cultural values, integrate those cultures into management practices, and create an inclusive and participatory environment. The proposed leadership model emphasizes the importance of flexibility, inclusivity, and respect for cultural diversity. The implications of this study show that a leadership approach that is responsive to cultural diversity can improve the effectiveness of management and the quality of education in Islamic educational institutions. The study also recommends the development of leadership training programs that focus on cultural diversity to strengthen leaders' ability to face complex challenges.